2010
DOI: 10.4067/s0718-19572010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Cross-frontal distribution of inorganic nutrients and chlorophyll-a on the Patagonian Continental Shelf of Argentina during summer and fall

Abstract: Resumen.-Datos oceanográficos recolectados durante 2001-2003 en la Plataforma Continental Patagónica Argentina fueron analizados para estudiar las principales características químicas en esta gran plataforma. Se presenta la variación de los nutrientes inorgánicos y de la clorofila-a a una distancia de 40 a 60 km de la costa. El nitrato es el nutriente limitante en la región y está negativamente correlacionado con la clorofila-a. Todas las variables presentan variaciones localizadas en verano, las cuales pueden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
3
16
1
1
Order By: Relevance
“…Stronger water column stratification in summer as compared to spring in the southern Patagonian shelf was also reported for the austral spring/summer season of 2005(Dogliotti et al, 2014. The range of nutrient concentrations observed in this study agrees with previous reports for the region (Paparazzo et al, 2010;Paparazzo, 2011;Balch et al, 2014;Valiadi et al, 2014). Even considering our relatively restricted study area, a subtle spatial variation in DIN distribution was observed at surface during the spring season.…”
Section: Taxonomic Groups Spring Summersupporting
confidence: 92%
“…Stronger water column stratification in summer as compared to spring in the southern Patagonian shelf was also reported for the austral spring/summer season of 2005(Dogliotti et al, 2014. The range of nutrient concentrations observed in this study agrees with previous reports for the region (Paparazzo et al, 2010;Paparazzo, 2011;Balch et al, 2014;Valiadi et al, 2014). Even considering our relatively restricted study area, a subtle spatial variation in DIN distribution was observed at surface during the spring season.…”
Section: Taxonomic Groups Spring Summersupporting
confidence: 92%
“…This would be the opposite under dominance of other groups and lower phytoplankton biomass [ Schloss et al , 2007]. A relatively low [ chl ] was observed associated to the coccolithophorid bloom found in this cruise, as compared to high concentrations measured in other bloom periods in the Patagonian shelf [ Carreto et al , 1995; Papparazzo et al , 2010] and shelf‐break [ Garcia et al , 2008; Ferreira et al , 2009]. However, even at lower biomass levels, organisms with calcium carbonate shells are known to modify CO 2 levels in the water column [ Zondervan , 2007], supporting the idea that the biological role in controlling gas concentration levels in the Patagonian region depends on the time of the year and the phytoplankton community.…”
Section: Discussionmentioning
confidence: 90%
“…8) (Romero et al, 2006;Paparazzo et al, 2010). Moreover, palaeobiogeographical studies have shown colder than present waters of higher productivity during the Late Pleistocene along Patagonia, especially in the southern sector.…”
Section: Accepted Manuscriptmentioning
confidence: 96%